Industrial crystallization process monitoring and control - Chianese, Angelo; Kramer, Herman J. M.; Wiley eBooks (Weinheim, Germany : Wiley-VCH, 2012)
"The first part of the book presents the instrumentation and techniques used to measure the crystal size distribution, the nucleation point and solubility point, and the chemical composition of the solid and liquid phase. The second part describes the main techniques adopted to control industrial crystallizers, starting from fundamental approaches to the most advanced ones, including the multivariable predictive control. An overview of the main crystallizer types is given with details of the main control schemes adopted in industry as well as the more suitable sensors and actuators. The contents are tailor-made for readers facing the threshold challenges between research and commercial applications."--Provided by publisher.
Includes bibliographical references and index.
John Wiley and Sons
Keywords: Crystallization -- Industrial applications; Crystallization; SCIENCE -- Chemistry -- Industrial & Technical; TECHNOLOGY & ENGINEERING -- Chemical & Biochemical; Crystallization; Crystallization -- Industrial applications; Electronic books